General view of university students Marmara University Vocational School of Health Services Case - ÖZNAZ, DEMET; BALIKCI, MURAT; AKYURT, NURAN (E D P SCIENCES, 2016)
The aim of this study was to determine the attitude towards the socio-economic conditions and demographic characteristics and the university life of medical students. To determine the students' socio-demographic characteristics Personal Information Form was used developed by researchers according to literature. The form contains expressions of the students such as the economic situation, future concerns, finding a job, university life, social & recreational activities, build up relationships with people and parents education level. Target group of the study were 349 students from Marmara University Vocational School of health. The environment of the survey was limited to the students studying in all programs at Marmara University Vocational School of Health. The research was carried out with students at Marmara University Vocational School of Health in the fall semester of 2014-2015.
Keywords: student profile; college life; vocational school students; health